Sociological Explanation of the Relationship between Social Trust and Social Tolerance Based on Giddens’ Structuration Theory - Vajihe Jalaeian Bakhshande; Vahid Ghasemi; mohammad taghi iman (توسعه اجتماعی)
In the theory of structuration, Giddens believes that structures facilitate the actions and also can not be reproduced without the agencies. The assumption of this study is that social trust and its dimensions (basic, interpersonal and institutional) can be affect social tolerance and its dimensions (structuration, expectations of the structure and expectations of the agency). The data obtained by using survey method and questionnaires with stratified random sampling (based on age, gender and area of residence) of 600 young people aged 18 to 29 in Isfahan. The results showed that 64% of variance of social tolerance explained by social trust and this variable has a high explanatory power. Social trust effect on social tolerance was also statistically significant (05/0 ≥ p). Respectively 62, 69 and 63 percent of social tolerance' dimensions variance explained by social trust. As a whole, the dimensions of social trust explained 46 percent of social tolerance variance.